Ceramic dielectric material capable of reducing sintering temperature of MLCC (multilayer ceramic capacitor) and preparation method of ceramic dielectric material

By modifying magnesium titanate and introducing a variety of components, a ceramic dielectric material with a high specific surface area is prepared, which solves the problems of high dielectric loss, poor temperature coefficient and high sintering temperature in the prior art, and achieves the effect of reducing the MLCC sintering temperature and optimizing the performance of the ceramic dielectric material.

CN119775000AActive Publication Date: 2025-04-08HANGZHOU XINGRONG TECH CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411988024.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

The dielectric loss of existing porcelain dielectric materials is high, and the temperature coefficient needs to be optimized. At the same time, the small specific surface area leads to a higher MLCC sintering temperature, which affects actual use.

Method used

By modifying the main crystal phase magnesium titanate and introducing components such as carbon-doped titanium dioxide, strontium zirconium titanate, yttrium modified alumina and lanthanum oxide composites, a ceramic dielectric material that can reduce the MLCC sintering temperature is prepared.

Benefits of technology

Multi-component synergistically reduces the dielectric loss of ceramic dielectric materials, obtains a good temperature coefficient, and reduces the MLCC sintering temperature through a high specific surface area.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005223025000000141
    Figure BDA0005223025000000141
Patent Text Reader

Abstract

The invention belongs to the technical field of ceramic materials, and particularly relates to a ceramic dielectric material capable of reducing the sintering temperature of an MLCC and a preparation method of the ceramic dielectric material. The ceramic dielectric material capable of reducing the sintering temperature of the MLCC is prepared by modifying the main crystalline phase magnesium titanate and introducing the components such as the carbon-doped titanium dioxide, the zirconium-containing strontium titanate, the yttrium-modified aluminum oxide and the lanthanum oxide composite material, the multiple components have a synergistic effect, the dielectric loss of the ceramic dielectric material is reduced, a good temperature coefficient is obtained, and the sintering temperature of the MLCC is reduced. And the sintering temperature of the MLCC is reduced through the high specific surface area.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of ceramic materials, and in particular relates to a ceramic dielectric material capable of reducing the sintering temperature of MLCC and a preparation method thereof. Background Art

[0002] Miniaturization, high performance and low energy consumption have become the main development trends of current electronic products such as mobile phones and computers. The integration and miniaturization of passive chip components such as capacitors, inductors and resistors used in these devices have also become an urgent need. Multilayer ceramic capacitors (MLCCs) have replaced single-layer ceramic capacitors as the current dominant capacitor product due to their high capacitance, high reliability, wide operating temperature and excellent high-frequency characteristics. Ceramic dielectric materials are a type of non-metallic materials with high insulation resistance, excellent temperature stability and mechanical strength. They are widely used in electronic components.

[0003] A Chinese patent (publication number CN112299839B) discloses a ceramic dielectric material for microwave high-stability and low-loss multilayer ceramic capacitors and its preparation method. The ceramic dielectric material of the invention limits the preparation method of the main crystal phase, so that the grain size of the main crystal phase is finer and the grain distribution is more uniform. The refined grains will produce more grain boundaries, which will be conducive to the diffusion of doped elements to improve the performance of the ceramic dielectric material; the added multiple components work together to make a large amount of liquid phase appear in the grain boundary during the sintering process of the ceramic dielectric material. The liquid phase has better fluidity, and the appearance of the liquid phase promotes the formation and growth of grains during sintering. However, the patent does not solve the problems of the high dielectric loss of the ceramic dielectric material in the prior art, the temperature coefficient needs to be optimized, and the small specific surface area leads to the need for a higher MLCC sintering temperature, which seriously affects its actual use.

[0004] Therefore, how to modify the main crystal phase of the ceramic material, optimize other component materials, reduce the dielectric loss of the ceramic material, obtain a good temperature coefficient, and reduce the MLCC sintering temperature through a high specific surface area has become a direction that needs to be focused on. Summary of the invention

[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a ceramic dielectric material and a preparation method thereof that can reduce the sintering temperature of MLCC, aiming to solve the problems of high dielectric loss of ceramic dielectric materials in the prior art, temperature coefficient to be optimized, and small specific surface area resulting in a higher MLCC sintering temperature.

[0006] The present invention prepares a ceramic dielectric material that can reduce the sintering temperature of MLCC by modifying the main crystalline phase magnesium titanate and introducing components such as carbon-doped titanium dioxide, strontium zirconate titanate, yttrium-modified alumina and lanthanum oxide composite materials. The multiple components work synergistically to reduce the dielectric loss of the ceramic dielectric material, obtain a good temperature coefficient, and reduce the sintering temperature of MLCC through a high specific surface area.

[0007] The technical solution adopted by the present invention to solve the above technical problems is as follows:

[0008] A first aspect of the present invention provides a method for preparing a ceramic material capable of reducing the sintering temperature of MLCC, comprising the following steps:

[0009] Step S1: by weight, add 2 to 4 parts of selenium powder and 3 to 5 parts of sodium borohydride to 300 to 400 parts of deionized water, stir and react for 4 to 6 hours under an argon atmosphere to obtain liquid A; add 2 to 4 parts of zinc acetate to 400 to 500 parts of anhydrous ethanol and mix evenly, adjust the pH to 10.2 to 10.6 with 1 mol / L sodium hydroxide solution, stir for 40 to 60 minutes under a nitrogen atmosphere to obtain liquid B; mix 300 to 400 parts of the liquid A and 400 to 500 parts of the liquid B evenly, heat and reflux at 80 to 90° C. for 2 to 4 hours to obtain a quantum dot solution, centrifuge, collect the precipitate, wash with anhydrous ethanol, and dry to obtain zinc selenide quantum dots;

[0010] Step S2: in parts by weight, 40 to 50 parts of magnesium oxide, 40 to 50 parts of titanium dioxide and 4 to 6 parts of zinc selenide quantum dots are mixed evenly, 400 to 500 parts of deionized water are added for ball milling to obtain a mixed powder, and the mixed powder is calcined at 1000 to 1100° C. for 4 to 6 hours to obtain modified magnesium titanate;

[0011] Step S3: In parts by weight, 90 to 100 parts of modified magnesium titanate, 6 to 8 parts of carbon-doped titanium dioxide, 6 to 10 parts of strontium titanate, 1 to 3 parts of aluminum oxide and 0.4 to 0.8 parts of lanthanum oxide are mixed evenly, ball-milled, dried, granulated, pressed into shape, and then sintered at 1120 to 1150°C for 4 to 6 hours to obtain a ceramic dielectric material that can reduce the sintering temperature of MLCC.

[0012] As a preferred technical solution of the present invention, the conditions of the ball milling treatment include: a ball milling speed of 300 to 400 r / min and a ball milling time of 20 to 24 h.

[0013] The zinc selenide quantum dots introduced into the modified magnesium titanate are of small size, can be evenly distributed in the magnesium titanate matrix and provide a large number of surface active sites, significantly increasing the total specific surface area of ​​the material; at the same time, the introduction of quantum dots will produce a certain amount of defects in the magnesium titanate lattice, and these defects can serve as additional active sites to further increase the specific surface area, and promote diffusion and reaction at lower temperatures through the high specific surface area, thereby achieving a reduction in the sintering temperature.

[0014] As a preferred technical solution of the present invention, the preparation method of carbon-doped titanium dioxide includes: in parts by weight, 60 to 70 parts of anhydrous ethanol, 20 to 30 parts of deionized water, 1 to 3 parts of itaconic acid and 6 to 8 parts of a 30% hydrochloric acid solution are mixed and stirred for 20 to 30 minutes, then 70 to 80 parts of tetrabutyl titanate are added and stirred for 40 to 60 minutes, the pH is adjusted to 3.2 to 3.6 with a 30% hydrochloric acid solution, and then 30 to 40 parts of deionized water are added and stirred for 120 to 180 minutes to form a gel, and the mixture is allowed to stand at room temperature for 12 to 14 hours, dried, and transferred to a tubular furnace for calcination at a calcination temperature of 500 to 540°C for a calcination time of 100 to 120 minutes, and cooled to room temperature to obtain carbon-doped titanium dioxide.

[0015] The carbon atoms in carbon-doped titanium dioxide can enter the titanium dioxide lattice, replace part of the oxygen or titanium atoms to form a solid solution, and obtain a mesoporous structure through the solid solution; at the same time, the presence of carbon atoms can inhibit the grain growth of titanium dioxide during the sintering process, maintain a smaller particle size, thereby increasing the specific surface area of ​​the ceramic material, and achieve a faster densification speed through the high specific surface area, thereby reducing the sintering temperature of the MLCC.

[0016] As a preferred technical solution of the present invention, the strontium titanate is strontium zirconate titanate; the preparation method of the strontium zirconate titanate comprises: adding 20 to 30 parts of strontium titanate and 0.3 to 0.5 parts of zirconium dioxide to 90 to 100 parts of anhydrous ethanol by weight, stirring for 40 to 60 minutes at 70 to 80°C, drying, grinding, and obtaining a mixed powder; uniformly mixing 1 to 3 parts of the mixed powder and 10 to 20 parts of strontium chloride hexahydrate, transferring to a muffle furnace for high-temperature treatment, centrifuging after the high-temperature treatment, washing with water, and drying to obtain strontium zirconate titanate.

[0017] As a preferred technical solution of the present invention, the conditions for high temperature treatment include: heating to 1060-1100°C at a heating rate of 10°C / min for a first insulation for 10-12 hours, then cooling to 860-900°C for a second insulation for 4-6 hours, and finally naturally cooling to room temperature.

[0018] The zirconium ions in strontium zirconate titanate have the same valence state as titanium ions, but the radius of zirconium ions is larger, which can effectively replace part of the titanium ions and enter the crystal lattice, thereby reducing the dielectric loss by reducing the formation of oxygen vacancies. At the same time, the introduction of zirconium can change the ferroelectric domain structure of strontium titanate, optimize the movement of domain walls, and reduce the energy dissipation of domain walls under AC electric fields, thereby reducing the dielectric loss of ceramic dielectric materials.

[0019] As a preferred technical solution of the present invention, the aluminum oxide is yttrium-modified aluminum oxide; the preparation method of the yttrium-modified aluminum oxide comprises: adding 40 to 50 parts of yttrium hydroxide and 90 to 100 parts of aluminum powder to 250 to 300 parts of a hydrochloric acid solution with a mass concentration of 10% by weight, stirring at 90 to 96° C. for 2 to 4 hours to form a sol; then adding 50 to 60 parts of cyclohexamethylenetetramine at 2 to 8° C. and mixing evenly, transferring to an aging reactor for aging treatment, washing, drying, roasting at 960 to 980° C. for 6 to 8 hours, and cooling to room temperature to obtain yttrium-modified aluminum oxide.

[0020] As a preferred technical solution of the present invention, the conditions of the aging treatment include: an aging temperature of 150 to 160° C. and an aging time of 4 to 6 hours.

[0021] Yttrium-modified alumina changes the conductive path of the material by introducing yttrium elements, effectively reducing leakage current and lowering the temperature dependence caused by leakage current; at the same time, the introduction of yttrium can reduce the microstructural heterogeneity inside the material and obtain a low temperature coefficient by reducing interface polarization.

[0022] As a preferred technical solution of the present invention, the lanthanum oxide is a lanthanum oxide composite material; the preparation method of the lanthanum oxide composite material comprises: adding 30 to 40 parts of lanthanum oxide and 2 to 4 parts of europium oxide to 200 to 240 parts of concentrated nitric acid by weight and mixing them evenly, then adjusting the pH to 8.2 to 8.6 with ammonia water, stirring for 20 to 30 minutes and then performing a hydrothermal reaction, washing the product with deionized water after the hydrothermal reaction is completed, and drying to obtain a precursor; transferring the precursor to a muffle furnace, calcining at 800 to 900° C. for 1 to 3 hours, and cooling with the furnace to obtain the lanthanum oxide composite material.

[0023] As a preferred technical solution of the present invention, the temperature of the hydrothermal reaction is 140-150° C. and the time is 24-30 hours.

[0024] The europium ions in the lanthanum oxide composite material can replace part of the lanthanum ions and enter the crystal lattice, stabilizing the cubic phase of lanthanum oxide, reducing phase change and defect formation, thereby improving the crystallinity and uniformity of the material, and reducing the temperature coefficient of the ceramic material by stabilizing the crystal structure.

[0025] The second aspect of the present invention provides a ceramic dielectric material that can reduce the sintering temperature of MLCC and is prepared by the method described in the first aspect.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] (1) The carbon-doped titanium dioxide of the present invention can obtain a mesoporous structure by carbon atoms entering the titanium dioxide lattice to form a solid solution. During the MLCC sintering process, the mesoporous structure with a high specific surface area can be used as a carrier to absorb the zinc selenide quantum dots of the modified magnesium titanate. At the same time, the zirconium element in the strontium zirconate titanate, the yttrium element in the yttrium-modified alumina and the europium element in the lanthanum oxide composite material will also partially migrate into the mesoporous structure and form a composite structure with the zinc selenide quantum dots at high temperature, effectively reducing the dielectric loss of the ceramic dielectric material and obtaining a good temperature coefficient. At the same time, the MLCC sintering temperature can be reduced by increasing the specific surface area.

[0028] (2) The zinc selenide quantum dots introduced into the modified magnesium titanate of the present invention have a small size, can be evenly distributed in the magnesium titanate matrix and provide a large number of surface active sites, significantly increasing the total specific surface area of ​​the material; at the same time, the introduction of quantum dots will produce a certain amount of defects in the magnesium titanate lattice, and these defects can serve as additional active sites to further increase the specific surface area; the carbon atoms in the carbon-doped titanium dioxide can enter the titanium dioxide lattice, replace part of the oxygen or titanium atoms to form a solid solution, and obtain a mesoporous structure through the solid solution; at the same time, the presence of carbon atoms can inhibit the grain growth of titanium dioxide during the sintering process, maintain a smaller particle size, thereby increasing the specific surface area of ​​the ceramic dielectric material, and achieving a faster densification speed through the high specific surface area, thereby reducing the sintering temperature of the MLCC.

[0029] (3) The zirconium ions in the strontium zirconate titanate of the present invention have the same valence state as the titanium ions, but the radius of the zirconium ions is larger, and they can effectively replace part of the titanium ions to enter the crystal lattice, thereby reducing the dielectric loss by reducing the formation of oxygen vacancies; at the same time, the introduction of zirconium can change the ferroelectric domain structure of strontium titanate, optimize the movement of the domain wall, and reduce the energy dissipation of the domain wall under the AC electric field, thereby reducing the dielectric loss of the ceramic dielectric material.

[0030] (4) The yttrium-modified alumina of the present invention changes the conductive path of the material by introducing yttrium elements, thereby effectively reducing leakage current and lowering the temperature dependence caused by leakage current; the europium ions in the lanthanum oxide composite material can replace part of the lanthanum ions and enter the crystal lattice, thereby stabilizing the cubic phase of lanthanum oxide, reducing phase change and defect formation, thereby improving the crystallinity and uniformity of the material, and reducing the temperature coefficient of the ceramic material by stabilizing the crystal structure. DETAILED DESCRIPTION

[0031] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0032] The sources of some components in the embodiments and comparative examples are as follows:

[0033] Magnesium titanate, CAS No. 12032-30-3, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0034] Titanium dioxide, CAS No. 13463-67-7, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0035] Strontium titanate, CAS No. 12060-59-2, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;

[0036] Alumina, CAS No. 1344-28-1, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;

[0037] Lanthanum oxide, CAS No. 1312-81-8, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;

[0038] Selenium powder, CAS No. 7782-49-2, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0039] Sodium borohydride, CAS No. 16940-66-2, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0040] Zinc acetate, CAS No. 557-34-6, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;

[0041] Anhydrous ethanol, CAS No. 64-17-5, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0042] Magnesium oxide, CAS No. 1309-48-4, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;

[0043] Hydrochloric acid, CAS No. 7647-01-0, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0044] Tetrabutyl titanate, CAS No. 5593-70-4, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;

[0045] Itaconic acid, product number PA54343, was purchased from Shanghai Chuangsai Technology Co., Ltd.;

[0046] Zirconium dioxide, CAS No. 1314-23-4, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;

[0047] Strontium chloride hexahydrate, CAS No. 10025-70-4, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0048] Yttrium hydroxide, CAS No. 16469-22-0, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;

[0049] Aluminum powder, CAS No. 7429-90-5, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0050] Cyclohexamethylenetetramine, CAS No. 100-97-0, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0051] Europium oxide, CAS No. 1308-96-9, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;

[0052] Concentrated nitric acid, CAS No. 7697-37-2, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0053] Ammonia water, CAS No. 1336-21-6, was purchased from Sinopharm Chemical Reagent Co., Ltd.

[0054] Example 1

[0055] This embodiment provides a method for preparing a ceramic material that can reduce the sintering temperature of MLCC, comprising the following steps:

[0056] Preparation of carbon-doped titanium dioxide: In parts by weight, 70 parts of anhydrous ethanol, 30 parts of deionized water, 3 parts of itaconic acid and 8 parts of 30% hydrochloric acid solution were mixed and stirred for 30 minutes, then 80 parts of tetrabutyl titanate were added and stirred for 60 minutes, the pH was adjusted to 3.6 with 30% hydrochloric acid solution, and then 40 parts of deionized water were added and stirred for 180 minutes to form a gel, which was allowed to stand at room temperature for 14 hours, dried, and transferred to a tubular furnace for calcination at a temperature of 540°C and a calcination time of 100 minutes. The mixture was cooled to room temperature to obtain carbon-doped titanium dioxide.

[0057] Preparation of strontium zirconate titanate: In parts by weight, 30 parts of strontium titanate and 0.5 parts of zirconium dioxide are added to 100 parts of anhydrous ethanol, stirred at 80°C for 60 minutes, dried, and ground to obtain a mixed powder; 3 parts of the mixed powder and 20 parts of strontium chloride hexahydrate are mixed evenly, and transferred to a muffle furnace for high-temperature treatment (heating to 1100°C at a heating rate of 10°C / min for a first insulation for 10 hours, then cooling to 900°C for a second insulation for 4 hours, and finally naturally cooling to room temperature), centrifuged after high-temperature treatment, washed with water, and dried to obtain strontium zirconate titanate.

[0058] Preparation of yttrium-modified alumina: In parts by weight, 50 parts of yttrium hydroxide and 100 parts of aluminum powder are added to 300 parts of 10% hydrochloric acid solution, and stirred at 96°C for 2 hours to form a sol; then 60 parts of cyclohexamethylenetetramine are added at 8°C and mixed evenly, and the mixture is transferred to an aging reactor for aging treatment (aging temperature is 160°C, aging time is 4 hours), washed, dried, calcined at 980°C for 6 hours, and cooled to room temperature to obtain yttrium-modified alumina.

[0059] Preparation of lanthanum oxide composite material: In parts by weight, 40 parts of lanthanum oxide and 4 parts of europium oxide are added to 240 parts of concentrated nitric acid and mixed evenly, then the pH is adjusted to 8.6 with ammonia water, and a hydrothermal reaction is carried out after stirring for 30 minutes (temperature is 150°C, time is 24 hours). After the hydrothermal reaction is completed, the product is washed with deionized water and dried to obtain a precursor; the precursor is transferred to a muffle furnace, calcined at 900°C for 1 hour, and cooled with the furnace to obtain a lanthanum oxide composite material.

[0060] Step S1: In parts by weight, 4 parts of selenium powder and 5 parts of sodium borohydride are added to 400 parts of deionized water, and stirred for reaction for 6 hours under an argon atmosphere to obtain liquid A; 4 parts of zinc acetate are added to 500 parts of anhydrous ethanol and mixed evenly, and the pH is adjusted to 10.6 with a 1 mol / L sodium hydroxide solution, and stirred for 60 minutes under a nitrogen atmosphere to obtain liquid B; 400 parts of the liquid A and 500 parts of the liquid B are mixed evenly, heated and refluxed at 90° C. for 2 hours to obtain a quantum dot solution, centrifuged, collected the precipitate, washed with anhydrous ethanol, and dried to obtain zinc selenide quantum dots;

[0061] Step S2: In parts by weight, 50 parts of magnesium oxide, 50 parts of titanium dioxide and 6 parts of zinc selenide quantum dots are mixed evenly, and 500 parts of deionized water are added for ball milling (the ball milling speed is 400 r / min, and the ball milling time is 20 h) to obtain a mixed powder, and the mixed powder is calcined at 1100° C. for 4 h to obtain modified magnesium titanate;

[0062] Step S3: In parts by weight, 100 parts of modified magnesium titanate, 8 parts of carbon-doped titanium dioxide, 10 parts of strontium zirconate titanate, 3 parts of yttrium-modified alumina and 0.8 parts of lanthanum oxide composite materials are mixed evenly, ball-milled, dried, granulated, pressed into shape, and then sintered at 1150°C for 4 hours to obtain a ceramic dielectric material that can reduce the sintering temperature of MLCC.

[0063] Example 2

[0064] This embodiment provides a method for preparing a ceramic material that can reduce the sintering temperature of MLCC, comprising the following steps:

[0065] Preparation of carbon-doped titanium dioxide: In parts by weight, 60 parts of anhydrous ethanol, 20 parts of deionized water, 1 part of itaconic acid and 6 parts of 30% hydrochloric acid solution were mixed and stirred for 20 minutes, then 70 parts of tetrabutyl titanate were added and stirred for 40 minutes, the pH was adjusted to 3.2 with 30% hydrochloric acid solution, and 30 parts of deionized water were added and stirred for 120 minutes to form a gel, which was allowed to stand at room temperature for 12 hours, dried, and transferred to a tubular furnace for calcination at a temperature of 500°C for 120 minutes. The carbon-doped titanium dioxide was obtained by cooling to room temperature.

[0066] Preparation of strontium zirconate titanate: In parts by weight, 20 parts of strontium titanate and 0.3 parts of zirconium dioxide are added to 90 parts of anhydrous ethanol, stirred at 70°C for 60 minutes, dried, and ground to obtain a mixed powder; 1 part of the mixed powder and 10 parts of strontium chloride hexahydrate are mixed evenly, and transferred to a muffle furnace for high-temperature treatment (heating to 1060°C at a heating rate of 10°C / min for a first insulation for 12 hours, then cooling to 860°C for a second insulation for 6 hours, and finally naturally cooling to room temperature), centrifuged after high-temperature treatment, washed with water, and dried to obtain strontium zirconate titanate.

[0067] Preparation of yttrium-modified alumina: In parts by weight, 40 parts of yttrium hydroxide and 90 parts of aluminum powder are added to 250 parts of 10% hydrochloric acid solution, and stirred at 90°C for 4 hours to form a sol; then 50 parts of cyclohexamethylenetetramine are added at 2°C and mixed evenly, and the mixture is transferred to an aging reactor for aging treatment (aging temperature is 150°C, aging time is 6 hours), washed, dried, calcined at 960°C for 8 hours, and cooled to room temperature to obtain yttrium-modified alumina.

[0068] Preparation of lanthanum oxide composite material: In parts by weight, 30 parts of lanthanum oxide and 2 parts of europium oxide are added to 200 parts of concentrated nitric acid and mixed evenly, then the pH is adjusted to 8.2 with ammonia water, and a hydrothermal reaction is carried out after stirring for 20 minutes (temperature is 140°C, time is 30 hours). After the hydrothermal reaction is completed, the product is washed with deionized water and dried to obtain a precursor; the precursor is transferred to a muffle furnace, calcined at 800°C for 3 hours, and cooled with the furnace to obtain a lanthanum oxide composite material.

[0069] Step S1: In parts by weight, 2 parts of selenium powder and 3 parts of sodium borohydride are added to 300 parts of deionized water, and stirred for reaction for 4 hours under an argon atmosphere to obtain liquid A; 2 parts of zinc acetate are added to 400 parts of anhydrous ethanol and mixed evenly, and the pH is adjusted to 10.2 with a 1 mol / L sodium hydroxide solution, and stirred for 40 minutes under a nitrogen atmosphere to obtain liquid B; 300 parts of the liquid A and 400 parts of the liquid B are mixed evenly, heated under reflux at 80° C. for 4 hours to obtain a quantum dot solution, centrifuged, collected the precipitate, washed with anhydrous ethanol, and dried to obtain zinc selenide quantum dots;

[0070] Step S2: In parts by weight, 40 parts of magnesium oxide, 40 parts of titanium dioxide and 4 parts of zinc selenide quantum dots are mixed evenly, and 400 parts of deionized water are added for ball milling (the ball milling speed is 300 r / min, and the ball milling time is 24 h) to obtain a mixed powder, and the mixed powder is calcined at 1000° C. for 6 h to obtain modified magnesium titanate;

[0071] Step S3: In parts by weight, 90 parts of modified magnesium titanate, 6 parts of carbon-doped titanium dioxide, 6 parts of strontium zirconate titanate, 1 part of yttrium-modified alumina and 0.4 parts of lanthanum oxide composite materials are mixed evenly, ball-milled, dried, granulated, pressed into shape, and then sintered at 1120°C for 6 hours to obtain a ceramic dielectric material that can reduce the sintering temperature of MLCC.

[0072] Example 3

[0073] This embodiment provides a method for preparing a ceramic material that can reduce the sintering temperature of MLCC, comprising the following steps:

[0074] Preparation of carbon-doped titanium dioxide: In parts by weight, 65 parts of anhydrous ethanol, 25 parts of deionized water, 2 parts of itaconic acid and 7 parts of 30% hydrochloric acid solution were mixed and stirred for 25 minutes, then 75 parts of tetrabutyl titanate were added and stirred for 50 minutes, the pH was adjusted to 3.4 with 30% hydrochloric acid solution, and 35 parts of deionized water were added and stirred for 160 minutes to form a gel, which was allowed to stand at room temperature for 13 hours, dried, and transferred to a tubular furnace for calcination at a temperature of 520°C and a calcination time of 110 minutes. The carbon-doped titanium dioxide was obtained by cooling to room temperature.

[0075] Preparation of strontium zirconate titanate: In parts by weight, 25 parts of strontium titanate and 0.4 parts of zirconium dioxide are added to 95 parts of anhydrous ethanol, stirred at 75°C for 50 minutes, dried, and ground to obtain a mixed powder; 2 parts of the mixed powder and 15 parts of strontium chloride hexahydrate are mixed evenly, and transferred to a muffle furnace for high-temperature treatment (heating to 1080°C at a heating rate of 10°C / min for a first insulation for 11 hours, then cooling to 880°C for a second insulation for 5 hours, and finally naturally cooling to room temperature), centrifuged after high-temperature treatment, washed with water, and dried to obtain strontium zirconate titanate.

[0076] Preparation of yttrium-modified alumina: In parts by weight, 45 parts of yttrium hydroxide and 95 parts of aluminum powder are added to 280 parts of 10% hydrochloric acid solution, and stirred at 94°C for 3 hours to form a sol; then 55 parts of cyclohexamethylenetetramine are added at 6°C and mixed evenly, and the mixture is transferred to an aging reactor for aging treatment (aging temperature is 155°C, aging time is 5 hours), washed, dried, calcined at 970°C for 7 hours, and cooled to room temperature to obtain yttrium-modified alumina.

[0077] Preparation of lanthanum oxide composite material: In parts by weight, 35 parts of lanthanum oxide and 3 parts of europium oxide are added to 220 parts of concentrated nitric acid and mixed evenly, then the pH is adjusted to 8.4 with ammonia water, and a hydrothermal reaction is carried out after stirring for 25 minutes (temperature is 145°C, time is 28 hours). After the hydrothermal reaction is completed, the product is washed with deionized water and dried to obtain a precursor; the precursor is transferred to a muffle furnace, calcined at 850°C for 2 hours, and cooled with the furnace to obtain a lanthanum oxide composite material.

[0078] Step S1: In parts by weight, 3 parts of selenium powder and 4 parts of sodium borohydride are added to 350 parts of deionized water, and stirred for reaction for 5 hours under an argon atmosphere to obtain liquid A; 3 parts of zinc acetate are added to 450 parts of anhydrous ethanol and mixed evenly, and the pH is adjusted to 10.4 with a 1 mol / L sodium hydroxide solution, and stirred for 50 minutes under a nitrogen atmosphere to obtain liquid B; 350 parts of the liquid A and 450 parts of the liquid B are mixed evenly, heated to reflux at 85° C. for 3 hours to obtain a quantum dot solution, centrifuged, collected the precipitate, washed with anhydrous ethanol, and dried to obtain zinc selenide quantum dots;

[0079] Step S2: In parts by weight, 45 parts of magnesium oxide, 45 parts of titanium dioxide and 5 parts of zinc selenide quantum dots are mixed evenly, 450 parts of deionized water are added for ball milling (the ball milling speed is 350 r / min, and the ball milling time is 22 h) to obtain a mixed powder, and the mixed powder is calcined at 1050° C. for 5 h to obtain modified magnesium titanate;

[0080] Step S3: In parts by weight, 95 parts of modified magnesium titanate, 7 parts of carbon-doped titanium dioxide, 8 parts of strontium zirconate titanate, 2 parts of yttrium-modified alumina and 0.6 parts of lanthanum oxide composite materials are mixed evenly, ball-milled, dried, granulated, pressed into shape, and then sintered at 1140°C for 5 hours to obtain a ceramic dielectric material that can reduce the sintering temperature of MLCC.

[0081] Comparative Example 1

[0082] This comparative example provides a method for preparing a ceramic dielectric material, which differs from Example 1 in that commercially available magnesium titanate is used instead of modified magnesium titanate, commercially available titanium dioxide is used instead of carbon-doped titanium dioxide, commercially available strontium titanate is used instead of strontium zirconate titanate, commercially available alumina is used instead of yttrium-modified alumina, and commercially available lanthanum oxide is used instead of lanthanum oxide composite materials.

[0083] Comparative Example 2

[0084] This comparative example provides a method for preparing an MLCC ceramic material, which differs from comparative example 1 in that modified magnesium titanate is used instead of commercially available magnesium titanate.

[0085] Comparative Example 3

[0086] This comparative example provides a method for preparing an MLCC ceramic material, which differs from comparative example 1 in that carbon-doped titanium dioxide is used instead of commercially available titanium dioxide.

[0087] Comparative Example 4

[0088] This comparative example provides a method for preparing an MLCC ceramic material, which differs from comparative example 1 in that strontium zirconate titanate is used instead of commercially available strontium titanate.

[0089] Comparative Example 5

[0090] This comparative example provides a method for preparing an MLCC ceramic material, which differs from comparative example 1 in that yttrium-modified alumina is used instead of commercially available alumina.

[0091] Comparative Example 6

[0092] This comparative example provides a method for preparing an MLCC ceramic material, which differs from comparative example 1 in that a lanthanum oxide composite material is used instead of commercially available lanthanum oxide.

[0093] Comparative Example 7

[0094] This comparative example provides a method for preparing a ceramic dielectric material, which differs from Example 1 in that commercially available magnesium titanate is used instead of modified magnesium titanate.

[0095] Comparative Example 8

[0096] This comparative example provides a method for preparing a ceramic dielectric material, which differs from Example 1 in that commercially available titanium dioxide is used instead of carbon-doped titanium dioxide.

[0097] Comparative Example 9

[0098] This comparative example provides a method for preparing a ceramic dielectric material, which differs from Example 1 in that commercially available strontium titanate is used instead of strontium zirconate titanate.

[0099] Comparative Example 10

[0100] This comparative example provides a method for preparing a ceramic dielectric material, which differs from Example 1 in that commercially available alumina is used instead of yttrium-modified alumina.

[0101] Comparative Example 11

[0102] This comparative example provides a method for preparing a ceramic dielectric material, which differs from Example 1 in that commercially available lanthanum oxide is used instead of the lanthanum oxide composite material.

[0103] The performance of the ceramic dielectric materials provided in the above embodiments and comparative examples was tested, and the testing method was as follows: the specific surface area test was carried out with reference to the requirements of "GB / T 5596-1996 Ceramic Dielectric Materials for Capacitors"; the ceramic dielectric materials prepared in the embodiments and comparative examples were coated with silver paste on both sides and silver electrodes were fired to make test samples, and the dielectric loss and temperature coefficient of the test samples were tested with reference to the requirements of "GB / T 5596-1996 Ceramic Dielectric Materials for Capacitors".

[0104] The above performance test data is shown in Table 1.

[0105] Table 1 Performance test results

[0106]

[0107] From the above content, it can be seen that the present invention prepares a ceramic material (Examples 1 to 3) that can reduce the sintering temperature of MLCC by modifying the main crystalline phase magnesium titanate and introducing carbon-doped titanium dioxide, strontium zirconate titanate, yttrium-modified alumina and lanthanum oxide composite materials. The specific surface area of ​​the ceramic material is 6183 to 6205 cm 2 / g, dielectric loss is 1.6×10 -4 ~1.9×10 -4 , the temperature coefficient TCC (125℃) is 9.7~10.2ppm / ℃.

[0108] Compared with Example 1, commercially available magnesium titanate is used to replace modified magnesium titanate, commercially available titanium dioxide is used to replace carbon-doped titanium dioxide, commercially available strontium titanate is used to replace strontium zirconate titanate, commercially available aluminum oxide is used to replace yttrium-modified aluminum oxide, and commercially available lanthanum oxide is used to replace lanthanum oxide composite materials, then the specific surface area is reduced, the dielectric loss is increased, and the temperature coefficient becomes larger (Comparative Example 1); compared with Comparative Example 1, modified magnesium titanate is used to replace commercially available magnesium titanate, then the specific surface area is increased (Comparative Example 2); compared with Comparative Example 1, carbon-doped titanium dioxide is used to replace commercially available titanium dioxide, then the specific surface area is increased (Comparative Example 3); compared with Comparative Example 1, strontium zirconate titanate is used to replace commercially available strontium titanate, then the dielectric loss is reduced (Comparative Example 4); compared with Comparative Example 1, yttrium-modified aluminum oxide is used to replace commercially available aluminum oxide, then the temperature coefficient becomes smaller (Comparative Example 5); compared with Comparative Example 1, the lanthanum oxide composite material is used Compared with Example 1, when commercially available magnesium titanate is used to replace modified magnesium titanate, the specific surface area is reduced, the dielectric loss is increased, and the temperature coefficient is increased (Comparative Example 7); compared with Example 1, when commercially available titanium dioxide is used to replace carbon-doped titanium dioxide, the specific surface area is reduced, the dielectric loss is increased, and the temperature coefficient is increased (Comparative Example 8); compared with Example 1, when commercially available strontium titanate is used to replace strontium zirconate titanate, the specific surface area is reduced, the dielectric loss is increased, and the temperature coefficient is increased (Comparative Example 9); compared with Example 1, when commercially available alumina is used to replace yttrium-modified alumina, the specific surface area is reduced, the dielectric loss is increased, and the temperature coefficient is increased (Comparative Example 10); compared with Example 1, when commercially available lanthanum oxide is used to replace the lanthanum oxide composite material, the specific surface area is reduced, the dielectric loss is increased, and the temperature coefficient is increased (Comparative Example 11).

[0109] In summary, the present invention prepares a ceramic dielectric material that can reduce the sintering temperature of MLCC by modifying the main crystalline phase magnesium titanate and introducing components such as carbon-doped titanium dioxide, strontium zirconate titanate, yttrium-modified alumina and lanthanum oxide composite materials. The multiple components work synergistically to reduce the dielectric loss of the ceramic dielectric material, obtain a good temperature coefficient, and reduce the sintering temperature of MLCC through a high specific surface area.

Claims

1. A method for preparing a ceramic material capable of reducing the sintering temperature of MLCC, characterized in that: The following steps are involved: Step S1: by weight, add 2 to 4 parts of selenium powder and 3 to 5 parts of sodium borohydride to 300 to 400 parts of deionized water, stir and react for 4 to 6 hours under an argon atmosphere to obtain liquid A; add 2 to 4 parts of zinc acetate to 400 to 500 parts of anhydrous ethanol and mix evenly, adjust the pH to 10.2 to 10.6 with 1 mol / L sodium hydroxide solution, stir for 40 to 60 minutes under a nitrogen atmosphere to obtain liquid B; mix 300 to 400 parts of the liquid A and 400 to 500 parts of the liquid B evenly, heat and reflux at 80 to 90° C. for 2 to 4 hours to obtain a quantum dot solution, centrifuge, collect the precipitate, wash with anhydrous ethanol, and dry to obtain zinc selenide quantum dots; Step S2: in parts by weight, 40 to 50 parts of magnesium oxide, 40 to 50 parts of titanium dioxide and 4 to 6 parts of zinc selenide quantum dots are mixed evenly, 400 to 500 parts of deionized water are added for ball milling to obtain a mixed powder, and the mixed powder is calcined at 1000 to 1100° C. for 4 to 6 hours to obtain modified magnesium titanate; Step S3: In parts by weight, 90 to 100 parts of modified magnesium titanate, 6 to 8 parts of carbon-doped titanium dioxide, 6 to 10 parts of strontium titanate, 1 to 3 parts of aluminum oxide and 0.4 to 0.8 parts of lanthanum oxide are mixed evenly, ball-milled, dried, granulated, pressed into shape, and then sintered at 1120 to 1150°C for 4 to 6 hours to obtain a ceramic dielectric material that can reduce the sintering temperature of MLCC.

2. The method for preparing a ceramic material capable of reducing the sintering temperature of MLCC according to claim 1, characterized in that: The ball milling treatment conditions include: a ball milling speed of 300 to 400 r / min and a ball milling time of 20 to 24 h.

3. The method for preparing a ceramic material capable of reducing the sintering temperature of MLCC according to claim 1, characterized in that: The preparation method of carbon-doped titanium dioxide comprises: mixing 60 to 70 parts of anhydrous ethanol, 20 to 30 parts of deionized water, 1 to 3 parts of itaconic acid and 6 to 8 parts of hydrochloric acid solution with a mass concentration of 30% by weight for 20 to 30 minutes, then adding 70 to 80 parts of tetrabutyl titanate and stirring for 40 to 60 minutes, adjusting the pH to 3.2 to 3.6 with a hydrochloric acid solution with a mass concentration of 30%, then adding 30 to 40 parts of deionized water and stirring for 120 to 180 minutes to form a gel, standing at room temperature for 12 to 14 hours, drying, transferring to a tubular furnace for calcination treatment, the calcination temperature is 500 to 540° C., the calcination time is 100 to 120 minutes, and cooling to room temperature to obtain carbon-doped titanium dioxide.

4. The method for preparing a ceramic material capable of reducing the sintering temperature of MLCC according to claim 1, characterized in that: The strontium titanate is strontium zirconate titanate; The preparation method of strontium zirconate titanate comprises: adding 20 to 30 parts of strontium titanate and 0.3 to 0.5 parts of zirconium dioxide to 90 to 100 parts of anhydrous ethanol by weight, stirring at 70 to 80° C. for 40 to 60 minutes, drying, grinding, and obtaining a mixed powder; uniformly mixing 1 to 3 parts of the mixed powder and 10 to 20 parts of strontium chloride hexahydrate, transferring the mixture to a muffle furnace for high-temperature treatment, centrifuging after the high-temperature treatment, washing with water, and drying to obtain strontium zirconate titanate.

5. The method for preparing a ceramic material capable of reducing the sintering temperature of MLCC according to claim 4, characterized in that: The conditions of the high temperature treatment include: heating to 1060-1100° C. at a heating rate of 10° C. / min for a first heat preservation of 10-12 hours, then cooling to 860-900° C. for a second heat preservation of 4-6 hours, and finally naturally cooling to room temperature.

6. The method for preparing a ceramic material capable of reducing the sintering temperature of MLCC according to claim 1, characterized in that: The aluminum oxide is yttrium-modified aluminum oxide; The preparation method of yttrium-modified alumina comprises: adding 40 to 50 parts of yttrium hydroxide and 90 to 100 parts of aluminum powder to 250 to 300 parts of hydrochloric acid solution with a mass concentration of 10% by weight, stirring at 90 to 96° C. for 2 to 4 hours to form a sol; then adding 50 to 60 parts of cyclohexamethylenetetramine at 2 to 8° C. to mix evenly, transferring to an aging reactor for aging treatment, washing, drying, roasting at 960 to 980° C. for 6 to 8 hours, and cooling to room temperature to obtain yttrium-modified alumina.

7. The method for preparing a ceramic material capable of reducing the sintering temperature of MLCC according to claim 6, characterized in that: The aging treatment conditions include: aging temperature of 150-160° C., and aging time of 4-6 hours.

8. The method for preparing a ceramic material capable of reducing the sintering temperature of MLCC according to claim 1, characterized in that: The lanthanum oxide is a lanthanum oxide composite material; The preparation method of the lanthanum oxide composite material comprises: adding 30 to 40 parts of lanthanum oxide and 2 to 4 parts of europium oxide to 200 to 240 parts of concentrated nitric acid by weight, and mixing them evenly; then adjusting the pH value to 8.2 to 8.6 with ammonia water; stirring for 20 to 30 minutes and then performing a hydrothermal reaction; after the hydrothermal reaction is completed, washing the product with deionized water, and drying to obtain a precursor; transferring the precursor to a muffle furnace, calcining at 800 to 900° C. for 1 to 3 hours, and cooling with the furnace to obtain the lanthanum oxide composite material.

9. The method for preparing a ceramic material capable of reducing the sintering temperature of MLCC according to claim 8, characterized in that: The temperature of the hydrothermal reaction is 140-150° C. and the time is 24-30 hours.

10. A ceramic dielectric material capable of reducing the sintering temperature of MLCC, characterized in that: Prepared according to the method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • A ceramic dielectric material for microwave high-stability, low-loss multilayer ceramic capacitors and its preparation method

    CN112299839B

  • Method for preparing low-temperature sintering ceramic dielectric material and obtained MLCC capacitor

    CN101671165A

  • Method for preparing high-dielectric active microwave medium ceramic material

    CN108911708A

  • High-dielectric ceramic capacitor dielectric material and preparation process thereof

    CN112159224A

  • High-hardness alumina-based ceramic and preparation method thereof

    CN118344128A